Implementation of Human Rights Protection Towards in Penitentiary of Children in Makassar - Mursyid Mursyid (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2019)
The urgency of child protection encourages a variety of efforts carried out by the government and society because it is considered not only to protect children as human beings but also as part of national development. Crimes or violations committed by the child then serve the sentence set by the juvenile justice process should still get full protection because it is considered the child still has a long future and the opportunity to build a nation after undergoing accountability errors that make it a human hope for the future come. The purpose of the study is to analyze the implementation of protection of human rights and the factors that influence the implementation of human rights protection for children in the Makassar Correctional Institution. As a result, the implementation of human rights against child prisoners is still less effective, because conceptually and in reality there has not yet been a clear difference between the implementation of human rights for adult prisoners. This study shows that there is no specific pattern that is applied in implementing human rights to children, where the practice of implementing child prisoner formation is still not in accordance with the basic idea, namely providing protection in order to achieve child welfare. The factors are legislation, facilities and infrastructure, organizational structure, human resources and administrative management, and not yet integrated handling of the implementation of human rights for child inmates by the entire criminal justice system.